A novel Drosophila serpin that inhibits serine proteases. - Han, J.; Zhang, H.; Min, G.; Kemler, D.; Hashimoto, C. (FEBS Letters, 2000)
Serpins define a large protein family in which most members function as serine protease inhibitors. Here we report the results of a search for serpins in Drosophila melanogaster that are potentially required for oogenesis or embryogenesis. We cloned and sequenced ovarian cDNAs that encode six distinct proteins having extensive sequence similarity to mammalian serpins, including residues important in the serpin inhibition mechanism. One of these new serpins in recombinant form inactivates, and complexes with, trypsin-like proteases in vitro. To our knowledge, these results represent the first evidence for a serpin in Drosophila that functions as a serine protease inhibitor.